White matter microstructure in youth with and at risk for bipolar disorder. (21st January 2020) - Linke, Julia O.; Stavish, Caitlin; Adleman, Nancy E.; Sarlls, Joelle; Towbin, Kenneth E.; Leibenluft, Ellen; Brotman, Melissa A.
Abstract: Objectives: Bipolar disorder (BD) and familial risk for BD have been associated with aberrant white matter (WM) microstructure in the corpus callosum and fronto‐limbic pathways. These abnormalities might constitute trait or state marker and have been suggested to result from aberrant maturation and to relate to difficulties in emotion regulation. Methods: To determine whether WM alterations represent a trait, disease or resilience marker, we compared youth at risk for BD (n = 36 first‐degree relatives, REL) to youth with BD (n = 36) and healthy volunteers (n = 36, HV) using diffusion tensor imaging. Results: Individuals with BD and REL did not differ from each other in WM microstructure and, compared to HV, showed similar aberrations in the superior corona radiata (SCR)/corticospinal tract (CST) and the body of the corpus callosum. WM microstructure of the anterior CC showed reduced age‐related in‐creases in BD compared to REL and HV. Further, individuals with BD and REL showed in‐creased difficulties in emotion regulation, which were associated with the microstructure of the anterior thalamic radiation. Discussion: Alterations in the SCR/CST and the body of the corpus callosum appear to represent a trait marker of BD, whereas changes in other WM tracts seem to be a disease state marker. Our findings also support the role of aberrant developmental trajectories of WM microstructure in the risk architecture of BD, although longitudinal studies are needed to confirm this association. Finally, our findings show the relevance of WM microstructure for difficulties in emotion regulation—a core characteristic of BD.